Influence of Writing Attribute on English Writing Performance of Pre-Service Technical Teachers - Olowoyeye Olowoyeye; Cyril Abioye Charles (Indonesian Journal Of Educational Research and Review, 2022)
This study examines the effect of writing attributes on the English writing performance of pre-service engineering teachers. This research adopts descriptive research with a survey type. The population for this study was all pre-service teachers. The target population is pre-service teachers in the three (3) selected Educational Colleges. A multi-stage sampling procedure was adopted for this study. The data collection instrument was an adapted questionnaire. Descriptive and inferential statistics were used to answer research questions and test the proposed hypothesis with product and service solution statistics (SPSS) version 20.0 at a significance level of 0.05. The findings show that pre-service teachers have sufficient attributes in writing English. There is no significant difference between male and female teachers' English writing in the South West. The study concludes that writing attributes are an essential element that determines pre-service teachers' performance in English, and there is no significant effect between pre-service teachers and women on their writing attributes. It is recommended that governments at all levels should provide schools with sufficient teachers, provide training and training opportunities for teachers, and grant grants and seminars for teaching staff.